Association Between Volatile Organic Compounds and Circadian Syndrome Among Pre- and Postmenopausal Women - Xiaoya Sun; Zhenao Zhang; Jingyi Ren; Huanting Pei; Jie Liu; Bowen Yin; Chongyue Zhang; Rui Wen; Simeng Qiao; Ziyi Wang; Yuxia Ma (Toxics)
Air pollution is closely associated with the development of multiple metabolic diseases. Circadian syndrome (CircS), as an extended concept of metabolic syndrome (MetS), has been proven to be a better predictor of metabolic diseases than MetS. However, the relationship between volatile organic compounds (VOCs) and CircS in pre- and postmenopausal women remains unclear. This study used data from the National Health and Nutrition Examination Survey (NHANES) 2011–2020, including 520 premenopausal women and 531 postmenopausal women. Generalized linear model (GLM), restricted cubic spline (RCS) model, subgroup analyses, and weighted quantile sum (WQS) model were used to assess the relationship between VOCs and CircS. In addition, sensitivity analyses were performed to evaluate the robustness of the results. Our findings showed that seven VOC metabolites were positively associated with the risk of CircS in postmenopausal women. In premenopausal women, only two VOC metabolites were positively associated with the risk of CircS. The WQS analysis further confirmed that VOC mixtures selected by a least absolute shrinkage and selection operator (LASSO) were significantly associated with an increased risk of CircS in postmenopausal women, with HPMMA identified as the primary contributor to the combined effect. This association was not evident in premenopausal women. Meanwhile, in postmenopausal women, individual urinary VOC metabolites and VOC mixtures were observed to be positively associated with elevated glucose and short sleep. Our results highlighted that VOC exposure was strongly associated with the occurrence of CircS in postmenopausal women. Further research is needed to confirm this conclusion.